Salmonella's iron armor for battling the host and its microbiota - Raffatellu, Manuela (Landes Bioscience, 2010)
Most Salmonella enterica serotypes are associated with acute intestinal inflammation and diarrhea in humans. While the mechanisms triggering intestinal inflammation are well studied, relatively little is known about how the pathogen benefits from causing disease. Recent work has provided first insights into the genetic design that enables S. enterica to benefit from the host response by outgrowing the microbiota in the gut. The pathogen gained an edge over its competitors by acquiring genes conferring resistance against antimicrobials, such as lipocalin-2, that are encountered in the intestinal lumen only during inflammation. This strategy enables the pathogen to exploit host responses to gain a competitive advantage over other microbes during its growth in the inflamed gut.